PERILAKU KOMUNIKASI PEMASARAN ONLINE OFFLINE MELALUI OMNICHANNEL DALAM MEMBANGUN USAHA MIKRO KECIL MENENGAH (UMKM) - ralin khairunnisah; Ratu Mutialela Caroboka; Rahma Santhi Zianaida; Bastian Zabir (Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial dan Politik Universitas Islam Negeri Raden Fatah Palembang, 2023)
The digital economy is a challenge for the government to make changes to business models in the business sector. Paradigm changes and perspectives in the field of marketing in the era of globalization are obligatory for business people. The omnichannel method can grow a loyal customer base. This study aims to observe the behavior of online offline marketing communications through omnichannel in building Micro, Small and Medium Enterprises (MSMEs). The research method used is qualitative with descriptive type. The approach used uses interviews, observation and in-depth study (in-depth approach). The sampling technique used is a purposive sample. The results of the study show: 1) Communication behavior that focuses on customer experience behavior, in the form of friendliness and real time response; 2) Behavior in using data as a preparation of marketing plans; 3) Behavior according to prospect segmentation and business flow personalization; 4) Behavior of communication with the application of relevant context marketing / context; 5) Social media approach through the right automation tools; and 6) Customer-centric communication behavior, placing potential customers as friends to establish synergistic communication with the aim of increasing customer loyalty.